Renal transplant: the perception of patients off waiting list in hemodialyis - Macilene Regina Pauletto; Margrid Beuter; Arlete Maria Brentano Timm; Naiana Oliveira Santos; Camila Castro Roso; Caren Silva Jacobi (Universidade Federal de Santa Maria, 2016)
Aim: to describe the perception about renal transplant of patients on hemodialysis that have not yet entered the waiting list. Method: this qualitative and exploratory study was developed with 15 patients on hemodialysis of a renal clinic. Data collection occurred from March to July 2012 through narrative interview of experiences. Data were submitted to thematic analysis. Results: patients see renal transplantation as a treatment that still requires care especially with medications, and involve risks such as infection, rejection and death. However, the transplant is perceived as the possibility of a better life, with more freedom and fewer restrictions. Conclusion: the positive and negative perceptions of patients about a renal transplantation influence their decision of entering a waiting list to perform a transplant, since it implies changes and limitations in their daily life for which they are not prepared yet